Performance of Saliva Samples for COVID-19 Diagnosis by Using the AllplexTM 2019-nCoV Assay Kit - Tapia, Cecilia V.; Marcia, Campos; Ivone, Mora; Nadia, Pozas; Lesly, Morales; Camila, Guzmán; Valentina, Aguilera; Paula, Ibarra; Fabien, Magne (Frontiers in Medicine, 2021)
Background: Although the nasopharyngeal swab (NPS) is the reference sampling method for the detection of SARS-Cov-2, it is not always possible to collect NPS in some patients. Saliva represents an interesting sampling method, as it is less invasive and more convenient in patients with nasal or pharyngeal lesions. Objective: To compare the RT-qPCR test performances of saliva samples with nasal mid-turbinate swab (NMTS) and NPS samples in a cohort of ambulatory patients suspected of having Covid-19. Study design: For each of 112 enrolled patients, NPS, NMTS and saliva samples were collected and tested for SARS-Cov-2 detection using three three different target genes (RdRP, N and E genes) by RT-qPCR. Results: Among the positive samples (56/112), saliva samples showed a lower percentage of SARS-Cov-2 detection compared to NPS samples, (85.7% vs 96.4%); while still lower percentage were observed for NMTS samples (78.6%). In average, saliva samples showed higher Ct values for all tested target genes, compared to those from NPS and NMTS samples. Conclusions: By using the AllplexTM 2019-nCoV Assay kit, saliva samples showed lower sensitivity for SARS CoV-2 compared to NPS samples, however the not detected cases had lower viral burden in NPS samples (CT values >33) representing an interesting alternative sampling method in patients in which is not possible to take a NPS sample.